EL Salvador : Ex Post Evaluation of Exceptional Access Under the 2009 Stand-By Arrangement. (IMF Staff Country Reports; Country Report, 2010)
The primary objective of the program was to prevent a crisis of confidence by signaling policy continuity and providing a liquidity buffer in case such shocks materialized. In addition, the program sought to preserve macroeconomic stability by focusing on sustaining fiscal prudence and financial sector reforms. IMF policy requires an ex post evaluation (EPE) of GRA-supported programs with exceptional access within a year after the end of the arrangement. Large provision of liquidity and effective use of IMF's lending facilities can be effective in preventing a crisis.